(untitled) (Journal of the College of Basic Education, 2022)
Reading is assumed to be the central tool for learning new information and gaining access to alternative explanations and interpretations .This study aims at finding out the effect of Using Jigsaw and Think - Pair - Share Techniques on the Development of the Reading Comprehension Skills of Iraqi Secondary School Students .To fulfill the aims of study , a non- randomized control group pre-test and post-test design have been applied to a sample of 85 from Al-Yarmouk Intermediate School for female. The study demands two experimental groups and a control one. The subjects of the three groups have been statistically matched according to their age (in months), their final scores in the previous exam (the midyear), and the academic level of their father and mother. Results, obtained by the statistical treatment of the data, have shown that: there is a statistically significant difference between the first experimental group, taught by jigsaw technique, and the control group, taught by traditional method of teaching in teaching reading comprehension, in favour of the first experimental group. There is a statistically significant difference between the second experimental group, taught by TPS technique, and the control group in teaching reading comprehension, in favour of the second experimental group. There is a statistically significant difference between the first experimental group and the second experimental one in teaching reading comprehension in favoure of the first experimental group. According to the results of the study, a number of recommendations are stated and suggestions for further studies are put forward.